2003
DOI: 10.1007/s00535-003-1230-8
|View full text |Cite
|
Sign up to set email alerts
|

Positron emission tomography with 2-deoxy-2-[ 18 F] fluoro-d-glucose for diagnosis of intraductal papillary mucinous tumor of the pancreas with parenchymal invasion

Abstract: We used positron emission tomography with 2-deoxy-2-[(18)F]fluoro- d-glucose (FDG-PET) in the diagnosis of two cases of malignant intraductal papillary mucinous tumor (IPMT) of the pancreas. A 56-year-old man and a 72-year-old man, both with tumors in the pancreatic head, were referred to Akita University Medical Center. Computed tomography revealed tumors with multiple cystic components in both patients. FDG-PET images showed markedly high FDG uptake in the area corresponding to a solid component found in one… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
8
0
1

Year Published

2005
2005
2013
2013

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 20 publications
(9 citation statements)
references
References 10 publications
0
8
0
1
Order By: Relevance
“…Several case reports have shown that an increased FDG uptake was observed in the mural nodules of malignant IPMN [15,16]. Baiocchi et al [17] have reported MRCP and PET findings of 7 patients with IPMN (2 malignant and 5 benign).…”
Section: Discussionmentioning
confidence: 97%
“…Several case reports have shown that an increased FDG uptake was observed in the mural nodules of malignant IPMN [15,16]. Baiocchi et al [17] have reported MRCP and PET findings of 7 patients with IPMN (2 malignant and 5 benign).…”
Section: Discussionmentioning
confidence: 97%
“…To our knowledge there are few reports dealing with PET imaging and cystic diseases of the pancreas. Yoshioka et al 28 reported a high 18-FDG uptake in two patients with IPMT and invasive carcinoma. On the other hand, McHenry et al 29 found that EUS fine-needle aspiration was more accurate (71%) than PET scan (50%) in detecting malignant cystic lesions.…”
Section: Discussionmentioning
confidence: 98%
“…However, recent reports have suggested that 18 F-fl uorodeoxyglucose positron emission tomography is more accurate than conventional imaging techniques (CT and magnetic resonance imaging) in distinguishing between the two. 11,12 In general, IPMN can be classifi ed into mainduct IPMN and side-branch IPMN based on imaging studies and histology. Main-duct and side-branch IPMN have signifi cant differences in their prevalence of cancer, thus this classifi cation has prognostic implications.…”
Section: Discussionmentioning
confidence: 99%